Relationship between supervisor conflict management styles and subordinate intention to leave - Zhao, Zhen Zhen (2008)
The purpose of this study is to investigate the relationship between supervisor conflict management styles and subordinate intention to leave in chemical industry in Tai'an City of China and to explore whether job opportunities and job tenure play moderating role in this relationship. A survey using questionnaire to collect data from 126 respondents from three companies in chemical industry in Tai'an City of China was conducted. The data reflects that the respondents perceive that integrating style and avoiding style are two mostly preferred conflict management styles of their supervisors in this study. Not all cooperative conflict management styles have negative relationship with subordinate intention to leave. Not all uncooperative conflict management styles have positive relationship with subordinate intention to leave. And job tenure has some moderating effect on the relationship, while job opportunities outside has no moderating role in the relationship. This paper generated important findings which are capable of enabling employers and employees of chemical industry in Tai'an City of China in understanding conflict and improving the effectiveness of conflict management.